ANALISIS KETERLAKSANAAN IMPLEMENTASI KURIKULUM 2013 DI KELAS 4 SD SE-KABUPATEN MAGETAN - Tryanasari, Dewi; Riyanto, Edy (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2014)
The curriculumin Indonesiahas beenamended several times, most recently in 2013. One of the districtsusedfortestingisMagetaninvolving11elemetary schools. The purpose of this researches to describe curriculum 2013 implementation of enforceability forfourth gradewholeMagetan. This research used aphenomenological approachtoqualitative research. theSubjects usedto teacher fourth gradeat theelementary school that used curriculum 2013. The object researchesthatexploredisthelearning, the learningprocess, andevaluationinstrumentsdeveloped bythe teacher. The collecting data techniqueincludesdocumentation, observationandinterviews. Researchersact asthe maininstrument in collecting data and add it i on al instrument form of field notes and checklist.The results showedthat: (1) theimplementation of thecurriculum 2013for fourth gradeinMagetannot fully yet implementedin terms oflearning plan development, learning implementation, andevaluation. This is happend becausethe mindsets of the teacher not complete yetchange. and thecommunity of society isnt involve yet in this case; and(2) the main obstaclein learning isimplementation about scientificapproachis not good yet, thatrequires studentstoinquirybasedprocess throughandcarefully plannedbythe teacher.Keywords: enforceability, implementation, curriculum 2013, fourth grade